2003
DOI: 10.1002/jsfa.1533
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in yellow‐ and red‐fleshed papaya (Carica papaya L)

Abstract: Vitamin A deficiency is a disorder of public health importance in Sri Lanka. A recent national survey revealed that 36% of preschool children in Sri Lanka have vitamin A deficiency (serum retinol <0.2 µg ml −1 ). In view of its well-established association with child morbidity and mortality, this is a reason for concern. One of the main fruits which has been recommended for prevention of vitamin A deficiency in Sri Lanka is papaya (Carica papaya L). In this study the carotenoid profiles of yellow-and red-flesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 11 publications
6
57
0
5
Order By: Relevance
“…It was observed that the β-carotene was significantly high in red fleshed papaya (700 μg/100 g DW) as compared to yellow-fleshed papaya (140 μg/100 g DW) [63]. The reasons suggested for the wide range in the β-carotene values were varietal differences, differences in maturity and ripening.…”
Section: Fruitsmentioning
confidence: 99%
“…It was observed that the β-carotene was significantly high in red fleshed papaya (700 μg/100 g DW) as compared to yellow-fleshed papaya (140 μg/100 g DW) [63]. The reasons suggested for the wide range in the β-carotene values were varietal differences, differences in maturity and ripening.…”
Section: Fruitsmentioning
confidence: 99%
“…The consumed fruit, rich in vitamins A and C, has been recommended for the prevention of vitamin A deficiency in some countries [1,2]. Two flesh colors, yellow and red, of papaya fruit are controlled by a single gene with yellow color as dominant [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Two flesh colors, yellow and red, of papaya fruit are controlled by a single gene with yellow color as dominant [3,4]. It has been previously documented that yellow-fleshed fruits have high amounts of the carotenoid β-cryptoxanthin and ζ-carotene but lack lycopene, whereas red-fleshed fruits have high amounts of lycopene along with β-cryptoxanthin, β-carotene, and ζ-carotene [2,5,6]. The red color of papaya fruit is due to the accumulation of lycopene; the yellow color is the result of converting lycopene to β -carotene and β-cryptoxanthin [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The flesh color of papaya druits is due to the presence of carotenoids. Redfleshed papaya fruits also comprised of five sub classes of carotenoids: beta-carotene, betacryptoxanthin, beta-carotene-5-6-epoxide, lycopene and zeta-carotene whilst, yellow-fleshed papaya contains only three subclasses of carotenoids: beta-carotene, beta-cryptoxanthin and zetacarotene (Chandrika et al, 2003). The concentration of b-carotene ranges from 866 to 7,807 μg/100g dry matter in ripe fruits (Puwastien et al, 2000;Saxholt et al, 2008).…”
mentioning
confidence: 99%